Peran Trust dalam Memediasi Pengaruh Perceived Ease of Use dan Perceived Usefulness Terhadap Online Repurchase Intention - Ni Luh Putu Widya Sawitri (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Online Repurchase Intention is an individual's intention to buy or reuse online something that has previously been purchased or used. This study aims to explain the effect of perceived ease of use and perceived usefulness on online repurchase intention with trust as a mediating variable. This research was conducted in Denpasar. The population of this research is people who have previously u transacted through Shopee e-commerce. The sampling technique used in this study is purposive sampling method, with 157 respondents. Data collection methods using google form questionnaire. Data analysis technique used is path analysis to determine the relationship between two variables and Sobel Test to determine the role of mediation. The results of this study found that perceived ease of use and perceived usefulness have positive and significant effect on trust and online repurchase intention, trust have a significant positive effect on online repurchase intention and trust mediated the perceived ease of use and perceived usefulness of online repurchase intention. Shopee needs to improve several aspects in order to increase online repurchase intention such as clarity and ease in understanding the usage procedures, lower product prices, increase user loyalty and increase innovation and promotion. Keywords : online repurchase intention, perceived ease of use, perceived usefulness, trust.